Paddy Yield as Affected by Boron Application Directly Sown on Raised Bed Under Saline Sodic Soils: Effect of Boron Levels on Rice Yield - Arshadullah, Muhammad; Hyder, Syed Ishtiaq; Ali, Arshad (Biological Sciences - PJSIR, 2012)